AVALIAÇÃO DA TOXICIDADE E ATIVIDADE ANTIOXIDANTE DAS FOLHAS, CASCAS E FRUTOS DE Solanum viarum DUNAL (SOLANACEAE) - GOMES, Paula Fernanda; DAMIÃO, Pamela Deniz; SILVA, Ana Francisca Gomes (ANAIS DO ENIC, 2023)
-